2019
DOI: 10.1128/jb.00597-18
|View full text |Cite
|
Sign up to set email alerts
|

Increased Intracellular Cyclic di-AMP Levels Sensitize Streptococcus gallolyticus subsp. gallolyticus to Osmotic Stress and Reduce Biofilm Formation and Adherence on Intestinal Cells

Abstract: Cyclic di-AMP is a recently identified second messenger exploited by a number of Gram-positive bacteria to regulate important biological processes. Here, we studied the phenotypic alterations induced by the increased intracellular c-di-AMP levels in Streptococcus gallolyticus, an opportunistic pathogen responsible for septicemia and endocarditis in the elderly. We report that an S. gallolyticus c-di-AMP phosphodiesterase gdpP knockout mutant, which displays a 1.5-fold higher intracellular c-di-AMP levels than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 73 publications
4
47
0
Order By: Relevance
“…Our success in creating a cdaA -deletion mutant was somewhat unexpected, since it has proven difficult to inactivate the sole diadenylate cyclase CdaA in several streptococci by conventional protocols. Whereas deletion of cdaA was possible in S. pyogenes [ 3 ] and S. mutans [ 45 , 46 ], all attempts to delete cdaA have been unsuccessful in S. pneumoniae [ 15 ] and S. gallolyticus [ 47 ]. In S. agalactiae , it was only possible to delete the chromosomal copy of cdaA in a strain carrying an inducible copy of cdaA on a plasmid [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our success in creating a cdaA -deletion mutant was somewhat unexpected, since it has proven difficult to inactivate the sole diadenylate cyclase CdaA in several streptococci by conventional protocols. Whereas deletion of cdaA was possible in S. pyogenes [ 3 ] and S. mutans [ 45 , 46 ], all attempts to delete cdaA have been unsuccessful in S. pneumoniae [ 15 ] and S. gallolyticus [ 47 ]. In S. agalactiae , it was only possible to delete the chromosomal copy of cdaA in a strain carrying an inducible copy of cdaA on a plasmid [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that inactivation of the main glycine betaine transporter OpuD (SAUSA300_1245) as well as the predicted amino acid transporter AlsT (SAUSA300_1252) allows an S. aureus dacA mutant to grow in rich medium in the absence of c‐di‐AMP (Zeden et al, ). In several other Firmicutes, including B. subtilis, Lactococcus lactis, Streptococcus pneumoniae, S. agalactiae, Streptococcus pyogenes and L. monocytogenes , inactivating mutations have also been identified in osmolyte and potassium transport systems that allow these bacteria to grow in the absence of c‐di‐AMP (Bai et al, ; Corrigan et al, ; Devaux et al, ; Fahmi et al, ; Gundlach, Commichau, et al, ; Gundlach, Herzberg, Hertel, et al, ; Pham et al, ; Pham & Turner, ; Quintana et al, ; Rocha et al, ; Teh et al, ; Whiteley et al, , ; Witte et al, ; Zarrella et al, ; Zeden et al, ) . This suggests that potassium and osmolyte transporters are more active in the absence of c‐di‐AMP, resulting in the accumulation of toxic levels of potassium and osmolytes in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The present results with pneumococcus grown on solid media (a more biofilm-like condition) contrast with prior studies of these bacteria grown in a strictly planktonic liquid broth culture (26), suggesting that c-di-AMP metabolism varies across types of bacterial growth. This is plausible given the many roles c-di-AMP plays in bacterial physiology, including evidence that c-di-AMP itself helps determine planktonic vs. biofilm organization in streptococci (22,(35)(36)(37)(38). Some virulence factors, like pneumolysin which can induce macrophage cytotoxicity as observed here, are more strongly expressed in biofilm-like growth states of pneumococci (32,33).…”
Section: Discussionmentioning
confidence: 60%